Hydrostatic-Pressure Modulation of Band Structure and Elastic Anisotropy in Wurtzite BN, AlN, GaN and InN: A First-Principles DFT Study - Ilyass Ez-zejjari; Haddou El Ghazi; Walid Belaid; Redouane En-nadir; Hassan Abboudi; Ahmed Sali (Crystals)
III-Nitride semiconductors (BN, AlN, GaN, and InN) exhibit exceptional electronic and mechanical properties that render them indispensable for high-performance optoelectronic, power, and high-frequency device applications. This study implements first-principles Density Functional Theory (DFT) calculations to elucidate the influence of hydrostatic pressure on the electronic, elastic, and mechanical properties of these materials in the wurtzite crystallographic configuration. Our computational analysis demonstrates that the bandgap energy exhibits a positive pressure coefficient for GaN, AlN, and InN, while BN manifests a negative pressure coefficient consistent with its indirect-bandgap characteristics. The elastic constants and derived mechanical properties reveal material-specific responses to applied pressure, with BN maintaining superior stiffness across the pressure range investigated, while InN exhibits the highest ductility among the studied compounds. GaN and AlN demonstrate intermediate mechanical robustness, positioning them as optimal candidates for pressure-sensitive applications. Furthermore, the observed nonlinear trends in elastic moduli under pressure reveal anisotropic mechanical responses during compression, a phenomenon critical for the rational design of strain-engineered devices. The computational results provide quantitative insights into the pressure-dependent behavior of III-N semiconductors, facilitating their strategic implementation and optimization for high-performance applications in extreme environmental conditions, including high-power electronics, deep-space exploration systems, and high-pressure optoelectronic devices.